2006
DOI: 10.1103/physrevb.73.115202
|View full text |Cite
|
Sign up to set email alerts
|

Annealing of electron-, proton-, and ion-produced vacancies in Si

Abstract: Positron lifetime and Doppler measurements were performed on float-zone-refined and variously doped Czochralski-grown Si. The samples were irradiated by various particles ͑e − , p, Kr͒ with energies between 2 MeV and 245 MeV. Electron or proton irradiation gave rise to divacancies, whereas the damage from ion implantation ͑Kr͒ was mainly in the form of four-vacancy clusters, with only a small fraction of vacancies in the form of divacancies. In the case of impurity-lean Si, detailed isothermal annealing at var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
12
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 49 publications
3
12
0
Order By: Relevance
“…This discrepancy was attributed to vacancy aggregation at the temperature at which the V 2 become mobile, the resulting clusters being positron detectable but not optically active. A similar discrepancy was reported by Dannefaer et al [3][4][5], who explained it in terms of V 2 associating loosely with each other without clustering. However, Makhov and Lewis later suggested that vacancy clustering may well not lead to a clear change in PAS parameters, while the IR response is destroyed [6].…”
supporting
confidence: 82%
See 1 more Smart Citation
“…This discrepancy was attributed to vacancy aggregation at the temperature at which the V 2 become mobile, the resulting clusters being positron detectable but not optically active. A similar discrepancy was reported by Dannefaer et al [3][4][5], who explained it in terms of V 2 associating loosely with each other without clustering. However, Makhov and Lewis later suggested that vacancy clustering may well not lead to a clear change in PAS parameters, while the IR response is destroyed [6].…”
supporting
confidence: 82%
“…Pinning of V 2 by impurities has been invoked to explain the survival of vacancy defects in Cz-Si to temperatures of 500 C [3,8].…”
mentioning
confidence: 99%
“…Although an increase in leakage currents at the given irradiation fluences may be considerable (by more than an order of magnitude), it can likely be minimized by annealing. It is known that in the case of large local concentrations of irradiation-induced defects annealing can cause formation of vacancy and interstitial clusters [12,13]. Because of issues indicated above, annealing experiments on optimization of leakage currents and reverse resistance recovery time of diodes irradiated with high-energy heavy ions require careful preparation and electron microscope studies which are beyond the scope of the current work.…”
Section: Resultsmentioning
confidence: 99%
“…The beam intensity is hence at least 2 orders of magnitude higher than at conventional laboratory beam setups and still higher than comparable large scale facilities [9,10]. Using the remoderated beam with 5 Â 10 7 positrons=second in situ positron-electron annihilation parameters can now be measured and analyzed on a time scale of a minute, and hence roughly at least 10 times faster than with conventional laboratory based positron annihilation facilities [11]. It allows for specific studies of fast defect-annealing kinetics.…”
mentioning
confidence: 99%